Participation of quetiapine in oxidative stress and inflammation status in the treatment of drug overdose - Karina Sommerfeld-Klatta; Magdalena Łukasik-Głębocka; Ewelina Krawczak; Anna Stodolska; Barbara Zielińska-Psuja (Polskie Towarzystwo Farmaceutyczne, 2023)
Quetiapine (QT) belongs to the second generation of antipsychotics. It is mostly used to treat depression, bipolar disorder, and schizophrenia. During biotransformation via myeloperoxidase (MPO) QT is oxidized to quinoneimine and a reactive radical, which may contribute to the development of oxidative stress during intoxication. The coexisting inflammation may also significantly contribute to the disturbances in the course of QT poisoning. In this study, twenty-one patients poisoned with quetiapine were examined. The study aimed to assess the correlation between blood QT concentration and selected oxidative stress as well as inflammation biomarkers, such as MPO and C-reactive protein (CRP) levels in the serum of poisoned patients. The obtained results were related to the values of the control group consisting of 21 healthy people, untreated and not poisoned with the drug. In patients with a toxic QT concentration in the blood (3.15 ± 2.11 μg/mL), the activity of MPO and CRP serum level were significantly higher in comparison to the control group. The mean level of CRP in the study group was 76.74 mg/L, while in the control group only 1.86 mg/L. The increase in MPO activity and CRP blood level in patients after QT overdose may confirm the hypothesis of oxidative disorders arising during its biotransformation and concomitant inflammation. Statistically significant relationships between selected biomarkers and blood QT concentration, the patient's clinical condition and the type of therapy were demonstrated.